2015
DOI: 10.1080/07370016.2015.1087262
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Efficacy and Self-Regulation with Nutrition and Exercise Behaviors in a Community Sample of Adults

Abstract: This study examined the association of self-efficacy and self-regulation with nutrition and exercise behaviors. The study used a cross-sectional design and included 108 participants (54 men, 54 women). Nutrition behaviors (fruit/vegetable consumption, dinner cooking, and restaurant eating) and exercise were measured using total days in last week a behavior was reported. Instruments measuring self-efficacy and self-regulation demonstrated excellent Cronbach's alphas (.93 -.95). Path analysis indicated only frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…This highlights the need to develop interventions or technology that addresses the needs of these individuals who are not motivated to develop healthy behaviors and have little desire to make lifestyle changes. This lack of motivation could be a result of low self-efficacy for exercise behaviors, which is often closely related to physical activity levels (25, 105). Recently, it has been suggested that incorporating techniques such as motivational interviewing may increase motivation and self-efficacy (106).…”
Section: Factors Involved In Behavior Changementioning
confidence: 99%
“…This highlights the need to develop interventions or technology that addresses the needs of these individuals who are not motivated to develop healthy behaviors and have little desire to make lifestyle changes. This lack of motivation could be a result of low self-efficacy for exercise behaviors, which is often closely related to physical activity levels (25, 105). Recently, it has been suggested that incorporating techniques such as motivational interviewing may increase motivation and self-efficacy (106).…”
Section: Factors Involved In Behavior Changementioning
confidence: 99%
“…Their model associates the self-perception of physical self-efficacy, competence and acceptance as the contributors to one's self-esteem with regards to physical activity. Additionally, as Shieh et.al show self-efficacy has a direct association with adherence to exercise [23]. Building on the importance of psychological barriers to physical activity, many researchers have proposed technological interventions focus on behaviour change theories to increase the amount of activity people do in their day-to-day lives.…”
Section: Tracking and Motivational Toolsmentioning
confidence: 99%
“…This may be particularly useful for people with low self-efficacy, i.e. limited belief in one's own ability, who may struggle to engage in physical activity [10]. Bandura describes how the feeling of self-efficacy is one of the core factors involved in whether someone will complete an activity [11].…”
Section: Introductionmentioning
confidence: 99%